Polymer Pre‐Aggregation Enables Optimal Morphology and High Performance in All‐Polymer Solar Cells. Issue 3 (7th October 2019) - Xie, Boming; Zhang, Kai; Hu, Zhicheng; Fang, Huiyu; Lin, Baojun; Yin, Qingwu; He, Baitian; Dong, Sheng; Ying, Lei; Ma, Wei; Huang, Fei; Yan, He; et al.
Abstract : Herein, all‐polymer solar cells (all‐PSCs) are studied based on PTzBI:N2200 system processed from two different solvents, chlorobenzene (CB) and 2‐methyltetrahydrofuran (Me‐THF). It is found that the preaggregation of the donor and acceptor polymers in Me‐THF is the key factor that enables a drastic enhancement in cell efficiency from ≈1% (processed by CB) to ≈11% (processed by Me‐THF). When using CB as the solvent, both donor and acceptor polymers are well dissolved and mostly disaggregated. In contrast, the donor and acceptor polymers both exhibit strong aggregation in Me‐THF. As a result, the donor and acceptor blend films processed from Me‐THF exhibit pure domains with appropriate molecular packing structure, which leads to high charge mobilities (10 −3 –10 −4  cm 2  V −1  s −1 ) and fill factors (FFs; 75%), whereas the blend films processed by CB suffer from highly miscible and impure domains, hence decreasing the charge mobilities by 1–2 orders of magnitude compared with those of the corresponding pure films. The current work reveals that the polymer preaggregation is the key reason enabling optimal morphology and high performance in N2200‐based all‐PSCs, and this strategy may be potentially applied in other systems to optimize the morphology and performance of all‐PSCs. Abstract : The power conversion efficiency of N2200‐based all‐polymer solar cells (all‐PSCs) can be drastically enhanced from ≈1% to ≈11% by simply changing the solvent from chlorobenzene and 2‐methyltetrahydrofuran (Me‐THF). In‐depth investigations reveal that the preaggregation of donor (PTzBI) and acceptor (N2200) polymers in 2‐Me‐THF is the key to enable such high performance for N2200‐based all‐PSC device.